2015
DOI: 10.22463/17949831.506
|View full text |Cite
|
Sign up to set email alerts
|

Maternity in adolescents and its association with caesarean labor

Abstract: Objective: to evaluate the association between adolescence and cesarean section in women aged 10-19 years compared with those found in ages between 19 and 25 years, patients in a hospital, and determine its association with sociodemographic variables and neonatal in terms of prematurity, and Apgar low birth weight. Materials and Methods: a case-control study was performed using a simple random sampling, considering the calculation of a statistical sample. a total of 1,304 cases and 2,608 controls were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(27 reference statements)
0
1
0
1
Order By: Relevance
“…However, it should be noted, that when analyzing differences between adult and adolescent women in the pregnancy process, it has been demonstrated that there are no significant differences in maternal deaths in this age ranges (27)(28)(29).…”
Section: Palavrasmentioning
confidence: 99%
“…However, it should be noted, that when analyzing differences between adult and adolescent women in the pregnancy process, it has been demonstrated that there are no significant differences in maternal deaths in this age ranges (27)(28)(29).…”
Section: Palavrasmentioning
confidence: 99%
“…No obstante, cabe resaltar que, al analizar diferencias entre mujeres adultas y adolescentes en el proceso de la gestación, se ha demostrado que no hay contundencia ni diferencias significativas frente a la mortalidad materna en todos los rangos de edad (27)(28)(29).…”
Section: Introductionunclassified